The Donkey - Devkota, Laxmi Prasad (Literary Studies, 2015)
Of all quadrupeds the donkey happens to be the one credited by men with the least amount of animal intelligence. Its very name has become a word of abuse and contempt to be used against a friend or an acquaintance whom you regard as lacking in that degree of understanding that is necessary to a normal social being. The higher castes in India and Nepal do not touch the unintelligent brute and take a purifying bath after an accidental jostling. The worshippers of intellect on our side of the world have graded animals in the order of their brain qualities and put them down accordingly under the category of eatables and uneatable, the adorable and the contemptible. The donkey, like the sow, is the most contemptible and the most untouchable among the four-legged kind. It is positively a chamar or pariah in the hierarchy of animals. My mother, an orthodox Brahmin, accustomed to holy rites and prayers, used to warn me in my childhood against taking the donkey's name early in the morning. She positively believed that a full day's religious merit acquired through pious meditation and prayers would be totally forfeited on hearing the name of that ugly kind. The worship of intelligence carried to a religious pitch produces orthodox abhorrence of that variety. When the washerman's donkey is tinkling its bells along the road, you can see the start of the orthodox pedestrian and the scared expression in the eyes of religious ladies. The very sight is regarded as ominous by those who live by religious signs and symbols.